Environmental Imaginaries of the Middle East and North Africa - Burke, Edmund; Davis, Diana K. (Ohio University Press, 2011)
The landscapes of the Middle East have captured our imaginations throughout history. Images of endless golden dunes, camel caravans, isolated desert oases, and rivers lined with palm trees have often framed written and visual representations of the region. Embedded in these portrayals is the common belief that the environment, in most places, has been deforested and desertified by centuries of misuse. It is precisely such orientalist environmental imaginaries, increasingly undermined by contemporary ecological data, that the eleven authors in this volume question. This is the first volume to critically examine culturally constructed views of the environmental history of the Middle East and suggest that they have often benefitted elites at the expense of the ecologies and the peoples of the region. The contributors expose many of the questionable policies and practices born of these environmental imaginaries and related histories that have been utilized in the region since the colonial period. They further reveal how power, in the form of development programs, notions of nationalism, and hydrological maps, for instance, relates to environmental knowledge production.Contributors: Samer Alatout, Edmund Burke III, Shaul Cohen, Diana K. Davis, Jennifer L. Derr, Leila M. Harris, Alan Mikhail, Timothy Mitchell, Priya Satia, Jeannie Sowers, and George R. Trumbull IV